Updated peer review of the pesticide risk assessment for the active substance terbuthylazine in light of confirmatory data submitted. (19th September 2019) - ; Abdourahime, Himdata; Anastassiadou, Maria; Arena, Maria; Auteri, Domenica; Barmaz, Stefania; Brancato, Alba; Bura, Laszlo; Carrasco Cabrera, Luis; Chaideftou, Eugenia; Chiusolo, Arianna; Court Marques, Daniele; et al.
Abstract: The conclusions of EFSA following the peer review of the initial risk assessment carried out by the competent authority of the rapporteur Member State, the United Kingdom, for the pesticide active substance terbuthylazine are reported. The context of the peer review was that requested by the European Commission following the submission and evaluation of confirmatory data on groundwater metabolites. The conclusions were reached on the basis of the evaluation of the representative uses of terbuthylazine as a herbicide on maize and sorghum and taking into account the scientific opinion of the EFSA Panel on Plant Protection Products and their Residues (PPR) on the setting of health‐based reference values for metabolites of the active substance terbuthylazine. The reliable endpoints concluded as being appropriate for use in regulatory risk assessment, derived from the available studies and literature in the dossier peer reviewed, are presented. Concerns are identified.